(untitled) (Linguostylistic Studies, 2018)
The article is devoted to the notion of the linguistic picture of the world in the aspect of the linguistic stylistics. The linguistic picture of the world is the embodiment of the linguistic consciousness of the person, his/her intellectual, moral, and national features. The notion of linguistic image of the world expresses the specificity of human existence, its interconnection with the world. In view of this, we can argue that the linguistic world image reflects the lingvosophy of humans - the way of verbalization of reality in their linguistic consciousness. E. Pashkovsky’s lingvosophy is based on strong links with the history of the Ukrainian people, linguistic and national traditions. The key words of the writer’s literary texts are the concepts of time and space. The lexico-semantic field is characterized predominantly by individual authored lexemes, semantics of which reflects tragic, immoral and hopeless senses. Occasional names are related to the tragic event of Ukraine – the Chernobyl tragedy. Expressive epithets of the time image verbalize the moral degradation of the individual and the entire Ukrainian nation in the post-Soviet era. Е. Pashkovsky’s lingvosophy highlights universal human problems, the global history of mankind. This led to the actualization of the image of the world, the interaction of the concepts of time and space. The lexico-semantic field of the space contains images of Ukraine, Chernobyl, steppe, homeland, land, city, village. The figurative paradigm of the notion land verbalizes the actual spatial concept – the territory, the place of residence of a person, as well as the linguistic manifestation of the inner senses. The verbal embodiment of the philosophy of the national idea in the writer’s texts is reflected in the artistic opposition of the city (town) – village as a linguistic sign of the negative and positive space of human presence. Linguistic style of expressing semantics of the space is connected with the writer’s nationalistic lingvosophy.